A violência na escola: abordagens teóricas e propostas de prevenção - Paula E Silva, Joyce Mary Adam De [UNESP]; Salles, Leila Maria Ferreira (Setor de Educação da Universidade Federal do Paraná, 2010)
The objective of this text is maturing a reflection, by means of a revision of studies in the area, on the theoretical trends involved on current discussions on school violence. We try to characterize proposals of intervention in the school environment implemented for governmental initiative to prevent violence. These proposals have, as a core objective, the incentive of democratic relations at school. It is pointed in this study that this important incentive to install democratic relations is insufficient to prevent violence pertaining the school scope. The violence determinants go beyond the individual and group characteristics of the people involved, and they are not restricted to the school context. Thus, it is important that the violence prevention programs extend the reflection on the different aspects concerned to school violence.

O objetivo deste texto é proceder a uma reflexão, por meio de uma revisão de estudos na área, sobre as tendências teóricas que têm permeado a discussão sobre violência escolar. Busca-se caracterizar propostas de intervenção na escola, implementadas por iniciativa governamental, para prevenir violência e que têm como proposta central o incentivo às relações democráticas na escola. Aponta-se neste estudo que o incentivo às relações democráticas, embora importante, é insuficiente para trabalhar a violência no âmbito escolar. Os determinantes da violência extrapolam as características individuais e grupais dos indivíduos envolvidos e não se restringem às vivências do contexto escolar. Assim, é importante que os programas de prevenção à violência ampliem a reflexão sobre os diferentes aspectos presentes na violência escolar.
School violence: theoretical approaches and proposals of prevention
Keywords: school; violence; proposals of intervention; escola; violência; propostas de intervenção